Nimesulide induced Stevens Johnson Syndrome: a case report - Naikwadi, Shagupta A.; Jadhav, Rupali B. (International Journal of Basic & Clinical Pharmacology, 2017)
Adverse drug reactions to the prescribed medicines are the major obstacles in continuation of drug treatment. Stevens- Johnson Syndrome (SJS) is a severe, episodic, acute mucocutaneous reaction which is most commonly elicited by drugs and occasionally by infections. Common drugs associated with SJS are sulphonamide antibiotics, anticonvulsants, non- steroidal anti-inflammatory drugs (NSAIDS) and allopurinol. Nimesulide is an NSAID with analgesic and antipyretic properties. Here, we report a case of 21 years old male patient who developed Stevens Johnson Syndrome following ingestion of tablet Nimesulide. The patient was managed with parenteral corticosteroids, antibiotics, emollients, and supportive care. This case highlights the importance of Nimesulide and other NSAIDs as possible cause of SJS. Nimesulide has never been approved in countries like USA, Canada, Australia. But in India it is available as over the counter drug and is used for various indications like fever, myalgia, arthralgia. Therefore, the drugs which are banned outside India should be used with caution and practitioners should report all the adverse drug reactions to such drugs.